2011
DOI: 10.1111/j.1365-2486.2011.02390.x
|View full text |Cite
|
Sign up to set email alerts
|

Site-to-site variability and temporal trends of DOC concentrations and fluxes in temperate forest soils

Abstract: Here, we report site-to-site variability and 12-14 year trends of dissolved organic carbon (DOC) from organic layers and mineral soils of 22 forests in Bavaria, Germany. DOC concentrations in the organic layer were negatively correlated with mean annual precipitation and elevation whereas air temperature had a positive effect on DOC concentrations. DOC fluxes in subsoils increased by 3 kg ha À1 yr À1 per 100 mm precipitation or per 100 m elevation. The highest DOC concentrations were found under pine stands wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
45
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 86 publications
(51 citation statements)
references
References 54 publications
(71 reference statements)
6
45
0
Order By: Relevance
“…DOC is mostly mobilized at the forest floor (Borken et al, 2011). Stored in the soil or diffusively and slowly passing downwards, large parts of the DOC are absorbed or consumed by microorganisms, but when lateral flow and concentrated infiltration increase, net leaching of DOC increases as well.…”
Section: Model Solute Transportmentioning
confidence: 99%
See 2 more Smart Citations
“…DOC is mostly mobilized at the forest floor (Borken et al, 2011). Stored in the soil or diffusively and slowly passing downwards, large parts of the DOC are absorbed or consumed by microorganisms, but when lateral flow and concentrated infiltration increase, net leaching of DOC increases as well.…”
Section: Model Solute Transportmentioning
confidence: 99%
“…riod are similarly large, thus pointing to a negligible effect of forest disturbance on DOC leaching. Numerous studies have identified the forest floor as a DOC source (Borken et al, 2011;Michalzik et al, 2001). Windthrow generally causes a (short-term) pulse of above-and belowground litter (Harmon et al, 2011).…”
Section: Impact Of Stormsmentioning
confidence: 99%
See 1 more Smart Citation
“…for forests and open land, respectively, which correspond to typical or average C org terr runoff concentrations for temperate forest landscapes, based on two literature syntheses (Michalzik et al, 2001;Borken et al, 2011). C org terr fluxes, modelled by LPJ-GUESS, increased in all future scenarios, by 30Á43% depending on the scenario.…”
Section: Land Surface and Drainage Basinmentioning
confidence: 99%
“…For non-wetland areas, C org terr exports were not simulated dynamically, but were estimated based on typical runoff C org terr concentration values of 40 and 8 mg L (1 for forests and open land areas, respectively (Michalzik et al, 2001;Borken et al, 2011). Absolute export fluxes of C org terr from these land cover classes depended on ecosystem runoff, simulated dynamically by LPJ-GUESS.…”
Section: Acknowledgementsmentioning
confidence: 99%